Characterisation of a thermal plume evolving in a confined environment: application to fire in tunnel. (2015) - Saafi, Hatem; Mahmoud, Ahmedou Ould Mohamed; Maad, Rejeb Ben
This investigation analyses the behaviour of a turbulent thermal plume evolving in a horizontal tunnel. The thermal plume is created by a hot disk. First, we studied the evolution of the thermal plume without ventilation system. The study of the average and fluctuating thermal and dynamic fields shows three zones during the vertical evolution of the free plume. A first zone close to the source, serving to the plume supply in fresh air, is characterised by the apparition of three exhausts of the thermal plume. Followed by a second zone where the main escape undergoes a contraction. Finally, a third zone where the thermal plume accumulates and undergoes a flow upstream named backlayering and a flow downstream that borders the ceiling to leave by the free part of the tunnel. We then determined the effects of the source site and longitudinal ventilation on the plume structure.